First record of the genus Australonura Cassagnau 1980 (Collembola: Neanuridae) in the New World, with description of a new species from Paraguay - Palacios-Vargas, José G.; Deharveng, Louis (Zootaxa, 2014)
The genus Australonura Cassagnau 1980 is newly recorded from South America. The Patagonian species Paleonura limnophila (Cassagnau & Rapoport, 1962) and Paleonura friasica Cassagnau & Oliveira, 1990 are redescribed from type material and recombined in Australonura. A new species, A. paraguayensis sp. nov., is described from Paraguay and assigned to Australonura for its head tubercle arrangement. It differs from other species of the genus by its adjacent but separate dorso-internal tubercles of Abd. V.